FGF23 and Cardiovascular Structure and Function in Advanced Chronic Kidney Disease. Issue 9 (29th September 2022) - Halim, Arvin; Burney, Heather N.; Li, Xiaochun; Li, Yang; Tomkins, Claudia; Siedlecki, Andrew M.; Lu, Tzong-shi; Kalim, Sahir; Thadhani, Ravi; Moe, Sharon; Ting, Stephen M.S.; Zehnder, Daniel; et al.
Visual Abstract: Abstract : Key Points: The highest fibroblast growth factor 23 (FGF23) quartile had impaired VO2 Max and ventilatory exercise response patterns compared with the lowest FGF23 quartile. FGF23 was associated with changes in VO2 Max in advanced CKD and after restitution of the failing kidney by transplantation. FGF23 was only associated with the progression of left ventricular mass index in patients with advanced CKD, however this association was lost after adjustment for dialysis status in the final model and was not associated after kidney transplantation in all models. Background: Fibroblast growth factor 23 (FGF23) is a bone-derived phosphatonin that is elevated in chronic kidney disease (CKD) and has been implicated in the development of cardiovascular disease. It is unknown whether elevated FGF23 in CKD is associated with impaired cardiovascular functional capacity, as assessed by maximum exercise oxygen consumption (VO2 Max). We sought to determine whether FGF23 is associated with cardiovascular functional capacity in patients with advanced CKD and after improvement of VO2 Max by kidney transplantation. Methods: We performed secondary analysis of 235 patients from the Cardiopulmonary Exercise Testing in Renal Failure and After Kidney Transplantation (CAPER) cohort, which recruited patients with stage 5 CKD who underwent kidney transplantation or were waitlisted and hypertensive controls. All patients underwent cardiopulmonary exercise testing (CPET) and echocardiography and were followed longitudinally for 1 year after study enrollment. Results: Patients across FGF23 quartiles differed in BMI ( P =0.004) and mean arterial pressure ( P <0.001) but did not significantly differ in sex ( P =0.5) or age ( P =0.08) compared with patients with lower levels of FGF23. Patients with higher FGF23 levels had impaired VO2 Max (Q1: 24.2±4.8 ml/min per kilogram; Q4: 18.6±5.2 ml/min per kilogram; P <0.001), greater left ventricular mass index (LVMI; P <0.001), reduced HR at peak exercise ( P <0.001), and maximal workload ( P <0.001). Kidney transplantation conferred a significant decline in FGF23 at 2 months ( P <0.001) before improvement in VO2 Max at 1 year ( P =0.008). Multivariable regression modeling revealed that changes in FGF23 was significantly associated with VO2 Max in advanced CKD ( P <0.001) and after improvement after kidney transplantation ( P =0.006). FGF23 was associated with LVMI before kidney transplantation ( P =0.003), however this association was lost after adjustment for dialysis status ( P =0.4). FGF23 was not associated with LVMI after kidney transplantation in all models. Conclusions: FGF23 levels are associated with alterations in cardiovascular functional capacity in advanced CKD and after kidney transplantation. FGF23 is only associated with structural cardiac adaptations in advanced CKD but this was modified by dialysis status, and was not associated after kidney transplantation.